REFLEXIVE FORMATION OF PROFESSIONAL SELF-IDENTITY OF SCHOOLCHILDREN - L. Mahleeva; V. Kormakova; M. Lapina (Вестник Северо-Кавказского федерального университета, 2022)
The paper reveals the content of the concepts «self-identity», ((professional self-identity», «reflexive formation of professional self-identity of schoolchildren». Presents a study of levels of self-esteem of schoolchildren, as one of the indicators of the reflective component offormation ofprofessional identity of students. The training self knowledge is presented as an active method of working on the formation of an adequate level of self-esteem of students. It is concluded that reflection is an important component, the final component in assessing the effectiveness of the formation ofprofessional self-identity of schoolchildren.